Targeting KRAS Sensitizes Ferroptosis by Coordinately Regulating the TCA Cycle and Nrf2‐SLC7A11‐GPX4 Signaling in Hepatocellular Carcinoma - Jiaxin Zhang; Zuojia Liu; Wenjing Zhao; Chang Li; Fei Liu; Jin Wang (Smart Medicine, 2025)
ABSTRACT Oncogenic KRAS, a notorious driver of cancer progression, remains a therapeutic challenge. In hepatocellular carcinoma (HCC), KRAS overexpression correlates with tumor aggressiveness. Here, we demonstrate that NSC48160 induces HCC cell death by suppressing KRAS expression. Metabolomic profiling revealed that NSC48160 significantly enhances intracellular tricarboxylic acid (TCA) cycle activity and fructose metabolism, disrupting redox homeostasis, and triggering ferroptosis. Combining NSC48160 with the SLC7A11 inhibitor HG106 synergistically eliminated HCC cells in vitro and suppressed tumor growth in vivo. Mechanistically, NSC48160 indirectly inhibits the Nrf2‐SLC7A11‐GPX4 axis, as evidenced by ferroptosis‐pathway array assays. Specifically, NSC48160 downregulates Nrf2 expression, thereby suppressing its downstream targets GPX4 and SLC7A11, ultimately promoting ferroptosis. Our findings establish NSC48160 as a novel KRAS inhibitor that induces ferroptosis through metabolic and redox reprogramming, offering a promising therapeutic strategy for KRAS‐driven HCC.